Fabrication and characterization of ultra light SiC whiskers decorated by RuO2 nanoparticles as hybrid supercapacitors. Issue 23 (17th February 2016) - Chen, Junhong; Zhang, Yujie; Hou, Xinmei; Su, Lei; Fan, Huili; Chou, Kuo-Chih
Abstract : Ultra light SiC whiskers decorated by RuO2 nanoparticles fabricated combining carbon thermal reduction and a hydrothermal route were investigated as novel hybrid supercapacitors with improved performance. Abstract : Ultra light SiC whiskers decorated by RuO2 nanoparticles fabricated combining carbon thermal reduction and a hydrothermal route were investigated as novel hybrid supercapacitors with improved performance. The morphology and microstructure of the composite indicate that RuO2 nanoparticles are dispersed on the surface of SiC whiskers. The electrochemical behavior of the hybrid electrode systematically measured in 1.0 M H2 SO4 demonstrates that SiC whiskers can considerably improve the supercapacitance properties of RuO2 . The specific capacitance of RuO2 nanoparticles in the composite can be obtained as high as 1454.8 F g −1 with a mass ratio of RuO2 /modified SiC whiskers of 2 : 3. Moreover, the hybrid electrode displays a longer cycle life with a better capacitance retention (∼93.6%) than that of pure RuO2 after 2000 CV cycles.